2021
DOI: 10.3390/ma14071775
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Characterization of Paraffin/Mesoporous Silica Shape-Stabilized Phase Change Materials for Building Thermal Insulation

Abstract: The use of phase change materials (PCMs) is an attractive method for energy storage and utilization in building envelopes. Here, shape-stabilized phase change materials (SS-PCMs) were prepared via direct adsorption using mesoporous silica (MS) with different pore diameters as the support matrix. The leakage properties, microstructure, chemical structure, thermophysical properties, activation energy, thermal stability and thermal storage-release characteristics of paraffin and SS-PCMs were investigated. The res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…In recent years, mesoporous SiO 2 (MS) has been widely studied for its excellent properties such as high specific surface area and controllable pore size. 131,132 The pore size of MS is between 2 and 50 nm, which is smaller than that of the porous materials mentioned above. 133 Compared with pure PCMs, when the PCMs are adsorbed by MS, the melting point of PCMs will change greatly.…”
Section: Other Porous Materialsmentioning
confidence: 88%
“…In recent years, mesoporous SiO 2 (MS) has been widely studied for its excellent properties such as high specific surface area and controllable pore size. 131,132 The pore size of MS is between 2 and 50 nm, which is smaller than that of the porous materials mentioned above. 133 Compared with pure PCMs, when the PCMs are adsorbed by MS, the melting point of PCMs will change greatly.…”
Section: Other Porous Materialsmentioning
confidence: 88%
“…The results indicated that the composite PCM had high light–thermal conversion efficiency. Li et al [ 12 ] investigated the adsorption effect of mesoporous silica with different pore sizes on paraffin. It was found that the silica with the smallest pore diameter had the largest adsorption capacity for paraffin.…”
Section: Introductionmentioning
confidence: 99%